Nano-scale and amourphous materials : selected, peer reviewed papers from the IUMRS-ICA 2010, 11th IUMRS International Conference in Asia, September 25-28, 2010, Qingdao, China - Wang, Rongming; Wu, Ying; Wu, Xiaofeng (Materials science forum ;, 2011)
These 76 peer-reviewed papers cover the current understanding of researchers working in the fields of nano-materials and technology, bulk metallic glasses and high-entropy alloys. This is a handy guide to a field of ever-growing importance.